DMAP-assisted sulfonylation as an efficient step for the methylation of primary amine motifs on solid support - Naoum, Johnny N.; Chandra, Koushik; Shemesh, Dorit; Gerber, R. Benny; Gilon, Chaim; Hurevich, Mattan (Beilstein Journal of Organic Chemistry, 2017)
Several multistep strategies were developed to ensure single methylation of amines on solid support. These strategies rely on the introduction of the o-NBS protecting/activating group as a key step. We found that the state-of-the-art strategies fail for the methylation of several primary amine motifs, largely due to inefficient sulfonylation. Here we show that using the superior nucleophilic base DMAP instead of the commonly used base collidine as a sulfonylation additive is essential for the introduction of the o-NBS group to these amine motifs. DFT calculations provide an explanation by showing that the energy barrier of the DMAP intermediate is significantly lower than the one of the collidine. We demonstrate that using DMAP as a sole additive in the sulfonylation step results in an overall effective and regioselective N-methylation. The method presented herein proved highly efficient in solid-phase synthesis of a somatostatin analogue bearing three Nα-methylation sites that could not be synthesized using the previously described state-of-the-art methods.
Keywords: N-methylation; nucleophilic addition; solid phase; somatostatin; sulfonylation